Aholcocerus arorai Yakovlev & Singh, sp. n. - new species of Cossidae from Nicobar Islands (India) with world catalogue of the genus (Lepidoptera: Cossidae) - R. V. Yakovlev; N. Singh (SHILAP)
Aholcocerus arorai Yakovlev & Singh, sp. n., is described from India (Great Nicobar Island). A catalogue of the genus Aholcocerus Yakovlev, 2006 is provided. External appearance and distributional map of all the species of genus is illustrated.